Adopción del rol materno según la Teoría de Ramona Mercer, en pacientes atendidas en el Patronato de Amparo Social de la ciudad de Tulcán - Romo Chunes, Milena Daraynely (2025)
The maternal role is essential given that it establishes a bond, vital for the affection, protection and attention of the child during the first years of life; so, this research was aimed at implementing educational strategies to improve this maternal role in each one of the mothers. Diverse activities were developed to promote the improvement of children care to enhance this maternal bond among the mothers who attend the municipal Patronato in Tulcan city. The methodology used was a quantitative paradigm and used the empirical method, like the scientific observation, which allowed to collect valid and reliable data regarding the mother’s current problem of this research carried out. Additionally, theoretical methods such as the historic- logic, analytic-synthetic, and inductive-deductive were provided from the different forms of this research. For the diagnosis it was used the Adoption scale of the maternal role, whose indicators showed that a range from 203- 224, refers to a high adoption maternal role, from 181 to 202 refers to a medium scale of maternal role, from 56 to 180 represents a low scale role; the results showed that only 20% of the mothers associated to this research represented a high adoption scale, 70% of the mothers represented a medium adoption scale, and 10% low adoption scale. This is the main reason to implement the educational strategies that guarantee the adoption of the maternal role, improving the bond between the mother and the child, in patients who attend the social welfare Municipal Patronato in Tulcan city.